KONSEP HIMPUNAN DAN DIAGRAM VENN PADA SMP NEGERI 07 BENGKULU BERBASIS MULTIMEDIA - Mahdarena Mahdarena; Siswanto Siswanto; Sapri Sapri (UNIVED Press, 2016)
One of the competencies that must be mastered students currently studying mathematics in junior high school (SMP) and is listed in the RPP (lesson plan) made by the teacher of junior high school mathematics is able to complete the concept of sets and Venn diagrams. In the current study the concept of sets and Venn diagrams, mastery of competencies was very important because it will be the main prerequisite when students learn the concept of sets and Venn diagrams on the next steps. Difficulties faced by teachers of mathematics and junior high school students in the form of low level of understanding of the students about the concepts related to the concept of sets and Venn diagrams and low skills in mennyelesaikan concept of sets and Venn diagrams. With such a reality, the use of instructional media using Macromedia Flash is one of supporting the achievement of an effective learning objectives and easy to understand The concept of Association and Venn Diagram multimedia applications on SMP 07 Bengkulu generated based Multimedia can provide convenience to the teachers of secondary school (SMP) 07 State of Bengkulu in providing the subject matter of the concept of Association and Venn Diagrams in SMP Negeri 07 Bengkulu based Multimedia.Keywords: Macromedia Flash, Concepts Association and the Venn Diagram, SMP 07 Bengkulu based Multimedia